Effectiveness of Group Guidance Using Reframing Techniques to Reduce Toxic Disinhibition among Junior High School Students - Nidaul Ummah; Ahmad Syarqawi (Journal of General Education and Humanities, 2025)
This study aims to determine the effectiveness of group guidance services using the reframing technique in reducing toxic disinhibition behaviour among eighth-grade students at SMP Negeri 2 Panyabungan. This behaviour involves aggressive and inappropriate expressions in digital interactions, often triggered by perceived anonymity and low social control. The study employed a quantitative approach with a one-group pretest-posttest pre-experimental design. A total of six students (n=6) identified with toxic disinhibition behaviour participated in the intervention. Data were collected using a 30-item questionnaire, validated with a Cronbach’s Alpha reliability score of 0.734. The intervention consisted of two group guidance sessions, each lasting 40 minutes. The results showed a reduction in the average score from 99.67 to 84.33. The Wilcoxon test yielded a significance value of 0.028 (p < 0.05), indicating a statistically significant difference before and after the intervention. The results suggest that the reframing technique effectively helps students reflect on their thinking patterns and build better self-control in digital contexts. This study recommends incorporating reframing into school counselling as a strategic approach to address deviant behaviour in the digital age. The findings also support using cognitive behavioural strategies in adolescent counselling interventions.